Theoretical characterization and modal directivity investigation of the interaction noise for a small contra-rotating fan. (1st January 2020) - Dong, Bin; Jiang, Changyong; Liu, Xiang; Deng, Yi; Huang, Lixi
Highlights: Theoretical model built for characterizing interaction noise of contra-rotating fan. Aerodynamic interaction is modelled with clear physical explanation. More complex modal directivity is found for contra-rotating fan. Abstract: The interaction noise radiated from c ontra-r otating (CR) fans is theoretically characterized, focusing on the unsteady lift force caused by aerodynamic interaction between the front and rear rotors. In the formulation, blade section misalignments leading to blade sweep and lean are considered. It is demonstrated that the conventional stator-rotor interaction noise problem is a special case of the present model, whereas the rotor-stator case is not. The derived formula is intended to enhance the understanding of the interaction noise mechanisms and help devise noise control methods in CR fans. Modal directivities of lower-order interaction tones are investigated with the derived formula as an application example, which is generally validated by the experimental results. To extract the interaction tones from the measured acoustic data, the Vold-Kalman filter is applied, with which the influences of broadband noise are excluded. It is found that the modal directivity of interaction noise for CR fans is more complicated than that for conventional fans. Theoretically, the leading order thrust noise is found to peak along the rotation axis and plummet in the rotational plane. For the first-order mode, the predicted directivity exhibits a forward-leaning characteristic, which is in good agreement with the experimental result. The predicted directivity patterns of second- and third-order modes are dominated by the drag noise component and peak in the direction near the rotational plane.